Effect of vitamin D supplementation on assisted reproduction technology (ART) outcomes and underlying biological mechanisms: protocol of a randomized clinical controlled trial. The "supplementation of vitamin D and reproductive outcome" (SUNDRO) study - Alessio Paffoni; Edgardo Somigliana; Veronica Sarais; Stefania Ferrari; Marco Reschini; Sofia Makieva; Enrico Papaleo; Paola Viganò (BMC, 2019)
Abstract Background Vitamin D plays an important role in human physiology and pathology. The receptor for vitamin D regulates 0.5-5% of the human genome. Accordingly, vitamin D insufficiency has been shown to increase the risk of several diseases. In recent years, based on growing evidence, on a role of vitamin D has been also postulated in reproductive health both in animals and humans, especially in female fertility female fertility. In vitro fertilization success was shown to be higher in women with appropriate reserves of vitamin D. However a causal relation has not been demonstrated and randomized controlled trials testing the effectiveness of vitamin D supplementation in IVF are warranted. Methods This is a multicenter randomized double blinded placebo controlled study aimed at determining the benefits of vitamin D [25(OH)D] supplementation in improving clinical pregnancy rate in women undergoing IVF. Eligible women with a serum level of 25-hydroxyvitamin D [25(OH)D] < 30 ng/ml will be randomized. Recruited women will be given the drug (either 600,000 IU of 25(OH) D or placebo in a single oral administration) at the time of randomization. Two centres will participate and the sample size (700 women) is foreseen to be equally distributed between the two. Patients will be treated according to standard IVF protocols. Discussion The primary aim of the study is the cumulative clinical pregnancy rate per oocyte retrieval. Clinical pregnancy is defined as the presence of at least one intrauterine gestational sac with viable foetus at first ultrasound assessment (3 weeks after a positive human chorionic gonadotropin [hCG] assessment). Secondary outcomes include: 1) clinical and embryological variables; 2) oocyte and endometrium quality at a molecular level. To investigate this latter aspect, samples of cumulus cells, follicular and endometrial fluids will be obtained from a subgroup of 50 age-matched good-prognosis cases and controls. Trial registration The protocol was included in EudraCT on 22nd September 2015 with the registration number assigned '2015-004233-27'; it was submitted through the database of the Italian "Osservatorio Nazionale della Sperimentazione Clinica (OsSC)" - (National Monitoring Centre of Clinical Trials) to the National Competent Authority on 8th March 2016 and approved on 23rd June 2016.